Evaluation and Preference Ranking of Multinational Companies’ Maize Hybrids in Sundarbazar, Lamjung, Nepal - Sharma, Deepa; Subedi, Samskriti; Kandel, Bishnu Prasad (Genetics, Plant Breeding and Seed Science, 2025)
To evaluate the performance of ten multinational maize hybrids in comparison with nationally developed hybrid maize varieties, a field experiment was conducted during the summer season of 2022 using a randomized complete block design at Sundarbazar, Lamjung. The assessment of farmers’ preferences and the agronomic performance of crops in specific agroecological zones plays a crucial role in improving the productivity of any crop. This study aimed to identify superior genotypes, assess farmer preferences, and promote the adoption of high-yielding maize varieties. A total of 12 maize hybrids were evaluated with three replications at a farmer’s field in Sundarbazar, Lamjung, Nepal, from March to July 2022. Rampur Hybrid-10 and Khumal Hybrid Maize-2 were standard checks. Analysis of variance revealed significant differences among the genotypes for most quantitative traits, including plant height, ear height, days to physiological maturity, ear weight, ear length, and grain yield. Compared to the check variety Rampur Hybrid-10, all other hybrids produced lower grain yields. However, their yields were statistically similar to that of Khumal Hybrid Maize-2. Farmer participation in the selection process helped identify superior varieties through preference ranking based on desirable ear characteristics. Among the multinational hybrids, TX-369 and CP-808 were the most preferred by farmers. Therefore, these varieties are recommended for cultivation in the Sundarbazar region.